Дымка: повесть / В. Джемс ; перевод с английского М. А. Гершензон - Джемс Виль (Звери, вперед!, 2008)
Экземпляры: (20200110) / Инвентарный номер: 33478 / Цена: 172.70 / Сис.шифр: И / Авт.знак: Д40 / ГРНТИ: 17 / ББК: 84(7Сое)